Nonlinear Physical Oceanography A Dynamical Systems Approach to the Large Scale Ocean Circulation and El Niño, - Dijkstra, Henk A. (Atmospheric and Oceanographic Sciences Library,, 2005)
In this book, methodology of dynamical systems theory is applied to investigate the physics of the large-scale ocean circulation. Topics include the dynamics of western boundary currents such as the Gulf Stream in the Atlantic Ocean and the Kurosio in the Pacific Ocean, the stability of the thermohaline circulation, and the El Niño/Southern Oscillation phenomenon in the Tropical Pacific. The book also deals with the numerical methods to apply bifurcation analysis on large-dimensional dynamical systems, with tens of thousands (or more) degrees of freedom, which arise through discretization of ocean and climate models. The novel approach to understand the phenomena of climate variability is through a systematic analysis of the solution structure of a hierarchy of models using these techniques. In this way, a connection between the results of the different models within the hierarchy can be established. Mechanistic description of the physics of the results is provided and, where possible, links with results of state-of-the-art ocean (and climate) models and observations are sought. The reader is expected to have a background in basic fluid dynamics and applied mathematics, although the level of the text sometimes is quite introductory. Each of the chapters is rather self-contained and many details of derivations are provided. Exercises presented at the end of each chapter make it a perfect graduate-level text. This book is aimed at graduate students and researchers in meteorology, oceanography and related fields who are interested in tackling fundamental problems in dynamical oceanography and climate dynamics.